2013
DOI: 10.3354/dao02630
|View full text |Cite
|
Sign up to set email alerts
|

Biliary cirrhosis caused by Campula spp. in a dolphin and four porpoises

Abstract: Biliary cirrhosis produced by Campula spp. is described in 1 striped dolphin Stenella coeruleoalba and 4 harbour porpoises Phocoena phocoena. The hepatic lesions consisted of severe proliferation of fibrous connective tissue with loss of the lobular pattern, nodular regeneration of the hepatic tissue, bile duct hyperplasia and severe inflammatory infiltrate composed of eosinophils, macrophages, lymphocytes and plasma cells. These lesions were associated with severe infestation by Campula spp. Although inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(23 reference statements)
0
12
1
Order By: Relevance
“…It has been suggested that these lesions could be associated with residual hepatic inflammation or systemic disease, 9 although 4 of 15 of the animals had no other significant inflammatory disease seen at necropsy. In fulminant trematode infections, there is portal inflammation and fibrosis, 10,12,15 and it is possible that these milder lesions may be associated with cleared or mild trematode infections that were not evident on postmortem examination. All cases of moderate or marked chronic hepatitis were associated with significant chronic inflammatory disease in other organ systems (multiorgan inflammation [Nos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that these lesions could be associated with residual hepatic inflammation or systemic disease, 9 although 4 of 15 of the animals had no other significant inflammatory disease seen at necropsy. In fulminant trematode infections, there is portal inflammation and fibrosis, 10,12,15 and it is possible that these milder lesions may be associated with cleared or mild trematode infections that were not evident on postmortem examination. All cases of moderate or marked chronic hepatitis were associated with significant chronic inflammatory disease in other organ systems (multiorgan inflammation [Nos.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recently, a study of the effects of Campula spp parasitism on the hepatobiliary system in cetaceans found severe architectural distortion caused by the trematodes with fibrosis, nodular regeneration, biliary hyperplasia, and inflammation. 10 The goals of this study were to describe the histologic liver lesions in very fresh to fresh (decomposition condition code [DCC] 1 and 2) 14 stranded harbor porpoises and to identify potential causes. Animals with trematode (Campula oblonga) infections were excluded for 3 reasons: the lesions have been described previously in great detail, 1,3,9,10,12,15,23 the parasites markedly distort the architecture with inflammation and cirrhosis that would mask other lesions, 10 and all livers with trematodes would be graded as very marked chronic hepatitis with very marked fibrosis, 7,8 which would potentially skew data analysis.…”
mentioning
confidence: 99%
“…On microbiological examination they found no clinically significant aerobic-anaerobic or fungal culture results from gastric contents. Jaber et al (2013) have described biliary cirrhosis produced by Campula spp. in 1 striped dolphin Stenella coeruleoalba and 4 harbor porpoises Phocoena phocoena.…”
Section: Dental Affectionsmentioning
confidence: 99%
“…It is caused by a combination of inflammation and activation of stellate cells in which it triggers an accumulation of extracellular matrix, and among other complex mechanisms, the role of macrophages including Kuppfer cells are considered important (30,31). In the case of hepatic trematodiasis in cetaceans, severe fibrosis is considered to be due to the physical presence of the parasite within bile ducts and exfoliated eggs around portal tracts (13). There have been several reports on the infiltrating inflammatory cell types (13,32,33), but details of the infiltrating and resident macrophages and the host's immune response have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hepatic trematodiasis in cetaceans, severe fibrosis is considered to be due to the physical presence of the parasite within bile ducts and exfoliated eggs around portal tracts (13). There have been several reports on the infiltrating inflammatory cell types (13,32,33), but details of the infiltrating and resident macrophages and the host's immune response have not been investigated.…”
Section: Introductionmentioning
confidence: 99%